Chronic food poverty in the Philippines - Connie Bayudan-Dacuycuy; Lora Kryz Baje (Philippine Institute for Development Studies (PIDS), 2017)
There are few studies in the Philippines that analyze poverty dynamics; and studies that analyze the effects of weather variability on food poverty dynamics are even fewer. Given that there are some sectors that are more adversely affected by the changing weather patterns, a study analyzing the effects of weather variability on poverty is essential. Using a simple spells approach to understand the food poverty dynamics in the Philippines, this paper finds that deviation of rainfall from its normal values and other key variables such as education, employment, assets, and armed conflict affect chronic food poverty. A discussion of some inputs to policies is provided.
Keywords: 330; chronic food poverty; rainfall; spells approach; Philippines